Free Berlin : art, urban politics, and everyday life - Smith, Briana J. (The MIT Press, 2022)
"First book to examine influential 1970s-1980s Berlin, a time of radical experimentation uniting art, urban politics, and everyday life that yielded enduring transformations in civic life"--